Exploring and Explaining Non-Compliance with Community Supervision. (10th November 2020) - Weaver, Beth; Piacentini, Laura; Moodie, Kristina; Barry, Monica
Abstract: Despite a developed theoretical and empirical body of research into the dynamics of compliance with community supervision, the phenomenon of non-compliance has received surprisingly less attention. This article explores the perspectives and experiences of 93 people in Scotland who were breached or recalled for non-compliance with the community sentences or post-release licences they were subject to. Drawing on this analysis, we advance an integrated, theoretically explanatory and empirically informed model demonstrating the contributions of, and interplay between, three key elements we identified as shaping non-compliance: motivational postures and attitudinal stances and their underlying mechanisms; various systemic, structural and social influences that bind the exercise of agency and shape situations of actions; and the impacts and effects of people's interactions with authorities.